Systematic review and meta-analysis of predictors of post-thyroidectomy hypocalcaemia. Issue 4 (9th January 2014) - Edafe, O; Antakia, R; Laskar, N; Uttley, L; Balasubramanian, S P
Abstract: Background: Hypocalcaemia is common after thyroidectomy. Accurate prediction and appropriate management may help reduce morbidity and hospital stay. The aim of this study was to perform a systematic literature review and meta-analysis of predictors of post-thyroidectomy hypocalcaemia. Methods: A systematic search of PubMed, EMBASE and the Cochrane Library databases was undertaken, and the quality of manuscripts assessed using a modified Newcastle–Ottawa Scale. Results: Some 115 observational studies were included. The median (i.q.r.) incidence of transient and permanent hypocalcaemia was 27 (19–38) and 1 (0–3) per cent respectively. Independent predictors of transient hypocalcaemia included levels of preoperative calcium, perioperative parathyroid hormone (PTH), preoperative 25-hydroxyvitamin D and postoperative magnesium. Clinical predictors included surgery for recurrent goitre and reoperation for bleeding. A calcium level lower than 1·88 mmol/l at 24 h after surgery, identification of fewer than two parathyroid glands (PTGs) at surgery, reoperation for bleeding, Graves' disease and heavier thyroid specimens were identified as independent predictors of permanent hypocalcaemia in multivariable analysis. Factors associated with transient hypocalcaemia in meta-analyses were inadvertent PTG excision (odds ratio (OR) 1·90, 95 per cent confidence interval 1·31 to 2·74), PTG autotransplantation (OR 2·03, 1·44 to 2·86), Graves' disease (OR 1·75, 1·34 to 2·28) and female sex (OR 2·28, 1·53 to 3·40). Conclusion: Perioperative PTH, preoperative vitamin D and postoperative changes in calcium are biochemical predictors of post-thyroidectomy hypocalcaemia. Clinical predictors include female sex, Graves' disease, need for parathyroid autotransplantation and inadvertent excision of PTGs. Abstract : Lack of proper definitions